The Impact of Cognitive-Behavioral Therapy on Decreased Symptoms of PTSD in Victims of Natural Disasters - Permatananda, Pande Ayu Naya Kasih; Tan, Ethan; Lim, Sofia (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Post-traumatic stress disorder (PTSD) is a significant mental health issue faced by individuals who have experienced natural disasters. Survivors of such events often endure long-lasting psychological effects, including flashbacks, hyperarousal, and emotional numbness, which hinder their ability to reintegrate into normal life. Cognitive-behavioral therapy (CBT) has emerged as an effective intervention for PTSD, offering tools for individuals to reframe distressing thoughts and regulate emotional responses. This study investigates the impact of CBT on the symptoms of PTSD in victims of natural disasters. The primary aim is to evaluate whether CBT can reduce the severity of PTSD symptoms in affected individuals. A quasi-experimental design was used, with 100 participants who were victims of a recent natural disaster. Participants underwent 8 weeks of CBT sessions, with pre- and post-assessment using the PTSD Checklist for DSM-5 (PCL-5). The results indicated a significant reduction in PTSD symptoms, with a marked decrease in both intrusive thoughts and hyperarousal behaviors. The findings suggest that CBT is an effective therapeutic approach for alleviating PTSD symptoms in disaster survivors. The study concludes that integrating CBT into post-disaster mental health care programs can significantly improve the well-being of disaster victims.